Molecular-oxygen-promoted Cu-catalyzed oxidative direct amidation of nonactivated carboxylic acids with azoles - Ding, Wen; Mai, Shaoyu; Song, Qiuling (Beilstein Journal of Organic Chemistry, 2015)
A copper-catalyzed oxidative direct formation of amides from nonactivated carboxylic acids and azoles with dioxygen as an activating reagent is reported. The azole amides were produced in good to excellent yields with a broad substrate scope. The mechanistic studies reveal that oxygen plays an essential role in the success of the amidation reactions with copper peroxycarboxylate as the key intermediate. Transamidation occurs smoothly between azole amide and a variety of amines.
Keywords: amidation; azoles; Cu-catalyzed; molecular oxygen; transamidation

(untitled) - Humphrey, M. J.; Chamberlin, R. A. (Chem. Rev., 1997)

(untitled) - Valeur, E.; Bradley, M. (Chem. Soc. Rev., 2009)

(untitled) - Mitchell, J. A.; Reid, E. E. (J. Am. Chem. Soc., 1931)

(untitled) - Shepard, E. E.; Porter, H. D.; Noth, J. F.; Simmans, C. K. (J. Org. Chem., 1952)

(untitled) - Schmidt, U.; Dietsche, M. (Angew. Chem., Int. Ed. Engl., 1982)

(untitled) - Cheung, C. W.; Fung, H. S.; Lee, S. Y.; Qian, Y. Y.; Chan, Y. W.; Chan, K. S. (Organometallics, 2010)

(untitled) - Das, S.; Biswas, R.; Mukherjee, B. (J. Phys. Chem. B, 2015)

(untitled) - Yoo, W.-J.; Li, C.-J. (J. Am. Chem. Soc., 2006)

(untitled) - Ekoue-Kovi, K.; Wolf, C. (Org. Lett., 2007)

(untitled) - Reddy, K. R.; Maheswari, C. U.; Venkateshwar, M.; Kantam, M. L. (Eur. J. Org. Chem., 2008)

(untitled) - Ghosh, S. C.; Ngiam, J. S. Y.; Chai, C. L. L.; Seayad, A. M.; Dang, T. T.; Chen, A. (Adv. Synth. Catal., 2012)

(untitled) - Prasad, V.; Kale, R. R.; Mishra, B. B.; Kumar, D.; Tiwari, V. K. (Org. Lett., 2012)

(untitled) - Hosseini-Sarvari, M.; Sharghi, H. (J. Org. Chem., 2006)

(untitled) - Ishihara, K.; Ohara, S.; Yamamoto, H. (J. Org. Chem., 1996)

(untitled) - Allen, C. L.; Chhatwal, A. R.; Williams, J. M. J. (Chem. Commun., 2012)

(untitled) - Goh, K. S.; Tan, C.-H. (RSC Adv., 2012)

(untitled) - Subramanian, P.; Indu, S.; Kaliappan, K. P. (Org. Lett., 2014)

(untitled) - Starkov, P.; Sheppard, T. D. (Org. Biomol. Chem., 2011)

(untitled) - Tan, B.; Toda, N.; Barbas, C. F., III (Angew. Chem., Int. Ed., 2012)

(untitled) - Charville, H.; Jackson, D.; Hodges, G.; Whiting, A. (Chem. Commun., 2010)

(untitled) - Kosal, A. D.; Wilson, E. E.; Ashfeld, B. L. (Chem. – Eur. J., 2012)

(untitled) - Dunlap, F. L. (J. Am. Chem. Soc., 1902)

(untitled) - Sheehan, J. C.; Hess, G. P. (J. Am. Chem. Soc., 1955)

(untitled) - Carey, J. S.; Laffan, D.; Thomson, C.; Williams, M. T. (Org. Biomol. Chem., 2006)

(untitled) - Punniyamurthy, T.; Velusamy, S.; Iqbal, J. (Chem. Rev., 2005)

(untitled) - Wang, T.; Jiao, N. (J. Am. Chem. Soc., 2013)

(untitled) - Ley, S. V.; Thomas, A. W. (Angew. Chem., Int. Ed., 2003)

(untitled) - Bi, H.-P.; Zhao, L.; Liang, Y.-M.; Li, C.-J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Liu, J.; Liu, Q.; Yi, H.; Qin, C.; Bai, R.; Qi, X.; Lan, Y.; Lei, A. (Angew. Chem., Int. Ed., 2014)

(untitled) - Pirovano, P.; Magherusan, A. M.; McGlynn, C.; Ure, A.; Lynes, A.; McDonald, A. R. (Angew. Chem., Int. Ed., 2014)

(untitled) - Horton, D. A.; Bourne, G. T.; Smythe, M. L. (Chem. Rev., 2003)

(untitled) - Yoon, J.; Solomon, E. I. (J. Am. Chem. Soc., 2007)

(untitled) - Kieber-Emmons, M. T.; Ginsbach, J. W.; Wick, P. K.; Lucas, H. R.; Helton, M. E.; Lucchese, B.; Suzuki, M.; Zuberbühler, A. D.; Karlin, K. D.; Solomon, E. I. (Angew. Chem., Int. Ed., 2014)

(untitled) - Bonnot, F.; Tremey, E.; von Stetten, D.; Rat, S.; Duval, S.; Carpentier, P.; Clemancey, M.; Desbois, A.; Nivière, V. (Angew. Chem., Int. Ed., 2014)